Designing a Human Resource Responsibility Model in Airline Companies Using Content Analysis Approach - Bayani Bandpey, Saeed; Zolfaghari Zafarani, Rashid; Haghighi, Masoud (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The objective of this study was to design a comprehensive model for human resource responsibility in the Islamic Republic of Iran Airline Company "Homa," addressing the increasing demands from consumers, investors, suppliers, and workers for organizational responsibility and the need for effective management of these activities and resource allocation.Methodology: The research employed a descriptive-analytical and inductive-deductive approach. Qualitative data were collected through interviews with 15 experts based on their specialization and experience in human resource management and organizational responsibility. Content analysis was used to extract and count relevant components from the literature, leading to the identification of 95 components. These were further categorized into six main components. The analysis was supported by the use of MAXQDA software for coding and categorization.Findings: The study identified 26 indicators within six main components of human resource responsibility: improving organizational welfare and health, responsible human resource behavior, engaging participation and developing a supportive reward system, developing the work environment, fostering constructive interaction, and enhancing human resource management functions.Conclusion: The results indicate that human resource responsibility in the Islamic Republic of Iran Airline Company "Homa" can be effectively modeled through the identified components and indicators. This model provides a structured framework for improving organizational practices, enhancing employee commitment and responsibility, and ultimately contributing to the organization's success. Managers can utilize these findings for strategic planning and decision-making to foster a culture of responsibility and ethical behavior within the organization.